2018
DOI: 10.1093/heapro/day026
|View full text |Cite
|
Sign up to set email alerts
|

Training of Mexican elders as health promoters: a qualitative study

Abstract: The purpose of the study was to analyze the repercussion of a training program in gerontological health promotion addressed to senior citizens in a rural area in Mexico. The impact of the program was examined at two levels: first, with regard to the development of specific practices relating to primary health care and to the actual implementation of community health programs and, second, through the interpretive analysis of bodily inscriptions in the participants. Results gave evidence of a gradual empowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This observation was also supported by one of the few studies to contrast evaluations of alternative programs, finding that participants in the PACE program had better outcomes than participants in another, less intensive, US federal program providing only coordination of care [21]. Narrowly-targeted interventions aimed at specific risks such as fall prevention [48][49][50][51] and suicide prevention [53] also appeared to have positive impacts. There was less evidence in support of educational programs in terms of impacting health outcomes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This observation was also supported by one of the few studies to contrast evaluations of alternative programs, finding that participants in the PACE program had better outcomes than participants in another, less intensive, US federal program providing only coordination of care [21]. Narrowly-targeted interventions aimed at specific risks such as fall prevention [48][49][50][51] and suicide prevention [53] also appeared to have positive impacts. There was less evidence in support of educational programs in terms of impacting health outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Other community health programs with more limited scope included health visitation and screening programs [38][39][40][41][42][43], mental health service programs [44], vaccination programs [45,46], meal programs [24,25,47], and prevention of specific health problems including falls [48][49][50][51], hypertension [37,52], and suicide [53]. Finally, less comprehensive and timelimited community health programs including education and fitness classes accounted for 18 of the programs evaluated (31.0%).…”
Section: Resultsmentioning
confidence: 99%
“…Their study also indicated that stronger social relationships are correlated with better subjective health ( Parra-Rizo and Sanchís-Soler, 2021 ). Psychological independence is also influenced by social capital, which is associated with being embedded in dense community networks ( Cornwell, 2011 ) and enables older persons to empower themselves to be “health promotors” in the community ( Martínez-Maldonado et al, 2019 ). Thus, as personal accountability is necessary to build strong bonds in a community, becoming empowered as a health promoter may encourage personal accountability in community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%